Vikings in the Gulf: fact or fancy? - Taylor, James Edgar (Proceedings of the Seminar for Arabian Studies, 2014)
In September 2007 in the journal of a respected learned society, a theory was published that medieval Vikings hauled two or more ships across the Isthmus of Suez and sailed through the Red Sea to the Persian Gulf, where they carved a number of petroglyphs of Viking ships on Jebel Jusasiyah in the Qatar peninsula. The evidential basis of the theory is: 1. A reference to a 'red sea' in the Icelandic saga of Ingvar the Far-Travelled; 2. A reference to Rūs travellers in the Kitāb al-masālik w-al-mamālik of Ibn Khurdādhbih; 3. The feasibility of such a journey; 4. The elimination of Arab ships as the model for the petroglyphs; 5. The identification of Viking ships as the model for the petroglyphs. The purpose of this paper is to carry out a critical examination of this evidence under each of the above headings, together with the author's stated reasons for deciding that the carvings are of Viking ships. If the theory is credible it constitutes a significant and hitherto unknown event in the history of the Gulf; if it is not it needs to be identified as such before it gathers momentum to become an unwelcome addition to the body of unsubstantiated speculations that clutter the field of research into the history of Arab ships and seafaring, creating a trap for the naive scholar who accepts statements at their face value. The paper includes ample background information to enable the non-specialist to follow the pros and cons of the argument.